Predictors of treatment interruption among tuberculosis patients in public health centres in Bali, Indonesia - Putu Ika Farmani; Dewa Nyoman Wirawan; Anak Agung Sagung Sawitri; I Wayan Gede Artawan Eka Putra (Public Health and Preventive Medicine Archive, 2017)
Background and purpose: Tuberculosis treatment interruption (TB TI) is one factor that leads to treatment failure, tuberculosis (TB) drug resistance and drop out. The purpose of this study is to identify the incidence and the predictors of TB TI in public health centres (PHCs) in Bali. Methods: A retrospective longitudinal study was conducted using secondary data of 644 cohorts of TB patients on the first regiment who enrolled in 11 PHCs in Denpasar Bali during 2011-2012. Information from TB program officers in PHCs was also obtained to determine the differences within the practical implementation of TB treatment. Data were analysed using Kaplan Meier and Cox Proportional Hazard Regression. Results: The study revealed that 378 patients experienced TB TI with the total events of 535. The incidence rate of TB TI event was 5.1 per 1.000 person days and the median time was 56 days (IQR: 56-57). Predictors of the TB TI were male (AHR=1.22; 95% CI: 1.02-1.45; p=0.027) and a more flexible schedule to take the medicine (AHR=1.47; 95%CI: 1.22-1.76; p<0.0001). Conclusions: The implementation of fixed schedule and shortened time lapse for patients to take TB drug will enable more close contact between patients and health providers. Intensive adherence counselling especially tailored for male patients is also required.